Reforming the individual income tax in Spain - Nezih Guner; Javier López-Segovia; Roberto Ramos (SERIEs - Journal of the Spanish Economic Association, 2020)
Can the Spanish government generate more tax revenue by making personal income taxes more progressive? To answer this question, we build a life-cycle economy with uninsurable labor productivity risk and endogenous labor supply. Individuals face progressive taxes on labor and capital incomes and proportional taxes that capture social security, corporate income, and consumption taxes. Our answer is yes, but not much. A reform that increases labor income taxes for individuals who earn more than the mean labor income and reduces taxes for those who earn less than the mean labor income generates a small additional revenue. The revenue from labor income taxes is maximized at an effective marginal tax rate of 51.6% (38.9%) for the richest 1% (5%) of individuals, versus 46.3% (34.7%) in the benchmark economy. The increase in revenue from labor income taxes is only 0.82%, while the total tax revenue declines by 1.55%. The higher progressivity is associated with lower aggregate labor supply and capital. As a result, the government collects higher taxes from a smaller economy. The total tax revenue is higher if marginal taxes are raised only for the top earners. The increase, however, must be substantial and cover a large segment of top earners. The rise in tax collection from a 3 percentage points increase on the top 1% is just 0.09%. A 10 percentage points increase on the top 10% of earners (those who earn more than exteuro41,699) raises total tax revenue by 2.81%.
Keywords: E21; E6; H2; J2; 330; Taxation; Progressivity; Top earners; Labor supply; Laffer curve